Strategi Dinas Kesehatan Dalam Penanganan Stunting di Kota Pekanbaru - Selphi Afdayati Dwi Putri; Dedi Kusuma Habibie (Jurnal Ilmiah Wahana Pendidikan, 2022)
Stunting is a condition where a child cannot grow up properly because lack of nutrition that makes the children grow shorter in their age. Stunting also can happen while the child is still in an embryo and a bad environment. So, the purpose of this research is what is the best strategy for public health service on how to handle stunting in Pekanbaru City (Case Study Of Rejosari Health Center) and the inhibiting factors for this strategy. The theoretical concept that researchers use is the theory of strategy implementation theory by wheelen and hunger with 3 factor, program, budgeting and procedure. Research uses qualitative research methods, with data collection techniques based on observations, interviews and documentation. The result of this research is the public health service strategy in handling stunting conditions on Pekanbaru City (Case Study Of Rejosari Health Center) is doing right, but in its implementation there are still obstacles and constraints such as the covid-19 pandemic factor and internal conditions of the Health Service and Rejosari Health Center.